Building Brand Awareness with Environmental Focus: Suasa Real Estate’s Instagram - Melati Budi Srikandi; Ni Made Prasiwi Bestari; Budi Shantika; I Putu Diva Putra (Faculty of Communication Science | Universitas Pancasila Jakarta, Indonesia, 2025)
This study examines the digital branding strategy of Suasa Real Estate on Instagram through the Circular Model of SOME (Share, Optimize, Manage, Engage). Situated in the rapidly developing and environmentally sensitive region of Canggu, Bali, Suasa’s Instagram presence offers a compelling case for understanding how luxury real estate brands build awareness, aesthetic appeal, and digital trust. The research reveals that Suasa’s 'Share' strategy excels in creating a consistent and aspirational visual identity, combining curated imagery, uniform design elements, and storytelling to position itself within the high-end property market. In the 'Optimize', the company utilizes Instagram Insights and tailored content formats, such as Reels and Highlights, to adapt posts to audience behavior, demonstrating a data-driven approach to increasing relevance and reach. The 'Manage' component reflects internal coordination efforts that ensure consistent posting schedules and organized visual presentation. However, findings show that the 'Engage' dimension, while partially successful in eliciting organic likes and comments, lacks mechanisms for two-way interaction. Audience interviews highlight a gap in participatory content, suggesting opportunities for improvement through features like Question and Answer (Q&A) polls, or user-generated content. Additionally, the study identifies an untapped potential in Suasa’s brand narrative: the integration of environmental messaging. Given Bali’s ecological concerns, embedding sustainability themes into visual and textual content could enhance brand trust and long-term relevance. This research concludes that the SOME model is a valuable framework for evaluating Instagram branding, and that future brand growth will depend on Suasa’s ability to merge aesthetic sophistication with interactive, and environmentally conscious storytelling.